2011
DOI: 10.1128/jvi.01925-10
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Hemagglutinin Tag Renders Lysine-Deficient APOBEC3G Resistant to HIV-1 Vif-Induced Degradation by Reduced Polyubiquitination

Abstract: APOBEC3G, a potent HIV-1 host restriction factor, is overcome by HIV-1 viral infectivity factor (Vif), which induces its polyubiquitination and proteasomal degradation. Here we show that lysine-deficient APOBEC3G with an N-terminal hemagglutinin (HA) tag fusion (HA-A3G20K/R) was resistant to HIV-1 Vif-induced proteasomal degradation. HA-A3G20K/R molecules were packaged into wild-type HIV-1 particles, and HA-A3G20K/R drastically decreased wild-type HIV-1 reverse transcription products and infectivity. We also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 81 publications
(133 reference statements)
1
34
0
Order By: Relevance
“…2A), as we previously showed that the N-terminus of A3G is an essential ubiquitin acceptor site [27]. When an HA-tag was fused to the N-terminus of lysine-free A3G (HAA3G20R), the A3G mutant was found to be resistant to Vif-induced degradation and its polyubiquitination modification was drastically reduced [27]. Therefore, using HAA3G20R as a template, we generated single arginine to lysine point reversions in A3G positions 297, 301, 303 and 334 (referred to as HAA3G297_K, HAA3G301_K, HAA3G303_K and HAA3G334_K, respectively).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…2A), as we previously showed that the N-terminus of A3G is an essential ubiquitin acceptor site [27]. When an HA-tag was fused to the N-terminus of lysine-free A3G (HAA3G20R), the A3G mutant was found to be resistant to Vif-induced degradation and its polyubiquitination modification was drastically reduced [27]. Therefore, using HAA3G20R as a template, we generated single arginine to lysine point reversions in A3G positions 297, 301, 303 and 334 (referred to as HAA3G297_K, HAA3G301_K, HAA3G303_K and HAA3G334_K, respectively).…”
Section: Resultsmentioning
confidence: 95%
“…Each revertant mutant harbors an HA-tag (YDYVPDYA) fused to the N-terminus (schematic shown in Fig. 2A), as we previously showed that the N-terminus of A3G is an essential ubiquitin acceptor site [27]. When an HA-tag was fused to the N-terminus of lysine-free A3G (HAA3G20R), the A3G mutant was found to be resistant to Vif-induced degradation and its polyubiquitination modification was drastically reduced [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these include APOBEC3G, TRIM5α, and tetherin (57, 58). APOBEC3G is incorporated into virus particles in an infected cell and when a new cell is infected it deaminates cytosines in the viral genome and inhibits reverse transcriptase (59). This results in the generation of mutations during reverse transcription essentially mutating the virus out of existence.…”
Section: Weak Iop Responsesmentioning
confidence: 99%
“…Similarly, the peroxisome proliferatoractivated receptor  co-activator 1 (PGC1) is primarily degraded through the nuclear N-terminus-dependent ubiquitin proteasome pathway (Trausch-Azar et al, 2010;Wang et al, 2011;Yang et al, 2009).…”
Section: N-terminal Ubiquitylationmentioning
confidence: 99%